2002
DOI: 10.1029/2001ja900160
|View full text |Cite
|
Sign up to set email alerts
|

Antisunward net Birkeland current system deduced from the Oersted satellite observation

Abstract: [1] From the precise magnetic field measurements by the Oersted satellite at low altitudes over various local times, a distinct spatial variation at middle and low latitudes was detected in the eastward component residuals (ÁB f ) after the subtraction of a geomagnetic main field model. The average ÁB f decreases on the dayside as latitude increases, and it increases on the nightside. That is, the latitudinal structure of the ÁB f has a negative trend in the northward direction on the dayside and a positive tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
16
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 17 publications
4
16
0
Order By: Relevance
“…This is also supported by other authors (e.g. Langel and Sweeney 1971;Iyemori 1990;Yamashita et al 2002) who found that residuals of Y and H components observed at the surface and at satellite altitude show a deflection in the same sense, thus implying that the source current is not in the ionosphere. The blue area of Fig.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…This is also supported by other authors (e.g. Langel and Sweeney 1971;Iyemori 1990;Yamashita et al 2002) who found that residuals of Y and H components observed at the surface and at satellite altitude show a deflection in the same sense, thus implying that the source current is not in the ionosphere. The blue area of Fig.…”
supporting
confidence: 78%
“…Evidences of net field-aligned currents have been discovered later in satellite observations (e.g. Yamashita et al 2002;Nakano and Iyemori 2003). According to Crooker and Siscoe (1981) they are expected to flow into the ionosphere on the day-side and out of the ionosphere on the night-side.…”
Section: Resultsmentioning
confidence: 99%
“…This model of the antisunward current system well explains not only the dawn‐dusk asymmetry of the north‐south geomagnetic disturbances but also the characteristics of the east‐west geomagnetic disturbances that the westward and eastward disturbances are seen on the dayside and nightside, respectively, as indicated by many low and middle latitudes ground observations [e.g., Grafe et al , 1986; Iyemori , 1990; Nakano et al , 2002]. Yamashita et al [2002] have shown that the antisunward current system explains the latitudinal magnetic field profile at low and middle latitudes even above the ionosphere by using the magnetic data from the Ørsted satellite. Suzuki and Fukushima [1984, 1998] have also derived the antisunward net currents from an Ampère's law integral along the Magsat orbit.…”
Section: Introductionmentioning
confidence: 61%
“…This model of the antisunward current system well explains not only the dawn-dusk asymmetry of the north-south geomagnetic disturbances but also the characteristics of the east-west geomagnetic disturbances that the westward and eastward disturbances are seen on the dayside and nightside, respectively, as indicated by many low and middle latitudes ground observations [e.g., Grafe et al, 1986;Iyemori, 1990;Nakano et al, 2002]. Yamashita et al [2002] have shown that the antisunward current system explains the latitudinal JOURNAL OF GEOPHYSICAL RESEARCH, VOL. 108, NO.…”
Section: Introductionmentioning
confidence: 68%
“…One of well‐known midlatitude east‐west magnetic disturbances caused by field‐aligned currents is a substorm current wedge effect, which indicates an eastward/westward disturbance in the premidnight and a westward/eastward disturbance in the postmidnight in the northern/southern hemisphere [ Clauer and McPherron , 1974]. On the other hand, an eastward/westward disturbance in the northern/southern hemisphere over the entire nightside is also common at midlatitudes (hereafter we will refer to eastward disturbances in the northern hemisphere and westward disturbances in the southern hemisphere as “positive” east‐west disturbances) [e.g., Iyemori , 1990; see also Yamashita et al , 2002]. These positive disturbances have been explained as a superposition of the effects of the Region 1 current system and those of the Region 2 current system by Nakano and Iyemori [2003].…”
Section: Introductionmentioning
confidence: 99%